Education Management of Modern Pesantren Gontor 10 Sabak - Rahman, K.A.; Yusup, Agung; Pratama, Firman Afrian; Mulyadi, Mulyadi; Huda, Rofiazka Fahmi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to evaluate the education management of the Gontor 10 Islamic Boarding School in Saba' as a consideration for the proposal to establish the Student Islamic Boarding School of the Center for Islamic Studies, Jambi University. The research method used is a qualitative descriptive approach with a field research approach and literature study. Primary data were obtained through observation and interviews, while secondary data was in the form of a SWOT analysis to evaluate the advantages, weaknesses, opportunities, and challenges in the education management of Gontor 10 Islamic Boarding School. The population of this study was Pondok Pesantren Gontor 10 Saba', with a research sample consisting of the head of the Islamic boarding school caregivers, teachers (ustadz), administrators, and students. The data analysis technique used is descriptive analysis to describe questionnaire and interview data findings. The results showed that the education management of Gontor 10 Islamic Boarding School has advantages in maintaining the values of modern boarding schools and improving the quality of education and teaching. However, there are weaknesses, especially in the availability of facilities and infrastructure and funding independence. Therefore, it is recommended that investment in the construction of facilities and infrastructure be increased, as well as diversification of funding sources to ensure the sustainability of superior programs.